1987
DOI: 10.1159/000284507
|View full text |Cite
|
Sign up to set email alerts
|

On the Daily Rhythm of Depression Symptomatology

Abstract: Diurnal variation of the symptomatology of endogenous depression (melancholy) was examined by means of 4 scales on 5 consecutive days in 24 untreated patients and in 63 patients under antidepressant drugs and after sleep deprivation. Results: the group means exhibit a sinus-type daily curve with morning low (but not significant). This so-called typical diurnal variation is more often found than other definable diurnal variations. The frequency cannot, however, be specified with one figure, because the quota va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 5 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…This is presumably a more severe form of depression (Hamilton, 1982). In a study of several different groups of depressed subjects, Tolle and Goetze (1987) found that a sinus-type daily curve, with a worsening of depressed feelings in the morning, was found more often than any other form of diurnal mood variation. In an early study of depression and daily variation and mood, Stallone, Huba, Lawlor, and Fieve (1973) followed 10 depressed inpatients over periods of up to 80 days.…”
Section: The Morning-worse Patternmentioning
confidence: 99%
“…This is presumably a more severe form of depression (Hamilton, 1982). In a study of several different groups of depressed subjects, Tolle and Goetze (1987) found that a sinus-type daily curve, with a worsening of depressed feelings in the morning, was found more often than any other form of diurnal mood variation. In an early study of depression and daily variation and mood, Stallone, Huba, Lawlor, and Fieve (1973) followed 10 depressed inpatients over periods of up to 80 days.…”
Section: The Morning-worse Patternmentioning
confidence: 99%
“…It was confirmed that diurnal mood variations in patients and healthy controls vary substantially from one day to the next [6][7][8]. Only a minority of probands displayed a specific diurnal variation type on 3 successive days according to all 3 instruments.…”
Section: Discussionmentioning
confidence: 61%
“…The frequency of the different types of diurnal variation seems to be virtually no different from that of depressive patients [7]. According to the few studies published on this aspect, typical diurnal variations among healthy controls are recorded with almost the same frequency [15] or with even greater frequency [16] than a lack of circadian mood rhythm, whereas inverse diurnal variations (with an evening low.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Many patients with non-seasonal depression show a regular daily pattern of symptoms, usually with more severe symptoms in the morning [72,73], while a minority show the opposite pattern known as ''reversed diurnal variation'' [74]. Healthy subjects typically report deterioration of mood in the evening compared to the morning [75,76].…”
Section: Circadian Rhythm Disturbances In Depressionmentioning
confidence: 99%